Candidate Genes for Suicide Risk in Head and Neck Squamous Cell Carcinoma Patients - Anusa Arunachalam Mohandoss; Rooban Thavarajah; Elizabeth Joshua; Umadevi Krishnamohan Rao; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2019)
Intoduction: Suicide is relatively more common among cancer patients as compared to general population. There are several identified candidate genes for suicide (CGS). There is a dearth of research examining the association of differential expression (DE) of CGS among the treatment-naïve head and neck squamous cell carcinoma (HNSCC) patients. The present study was undertaken to identify the DE of messenger Ribo Nucleic Acid (mRNA) of CGS in HNSCC tumor and correlate with clinical and other known genetic factors that promote oncogenesis as well as suicide. Material and Methods: Using previously described method, CGS lists were identified. The DE of the mRNA of the CGS were obtained from The Cancer Genome Atlas-HNSCC patients along with clinical details. The DE of mRNA pertaining to known factors such as inflammation, serotonergic, and dopaminergic functions as well as clinical parameters were studied for association with the risk of DE of CGS. Appropriate statistics were performed and P ≤ 0.05 was taken as significant. Results: A total of 520 HNSCC patients formed the study group. There were 46 (8.85%) patients who had DE of CGS. Expression of genes associated with inflammatory signaling pathway, ribosomal protein pathway, mechanistic Target of Rapamycin (mTOR), and metastasis, and invasion set of genes as well as the noradrenergic group of genes were associated significantly with DE of CGS. The association of DE of CGS and the major HNSCC clinical predictors of smoking, human papilloma virus status, clinical and cancer staging, histology grading, as well as patient status were not statistically significant. With a male predilection, gender exhibited statistically significant difference (P = 0.012). Discussion: In cancer patients, transcriptomes have been postulated to mediate suicide by targeted action on human brain. DE of putative genes associated with suicide have been demonstrated in HNSCC tumor. These DEs could predispose the patients to suicidal ideation/behavior in confluence with immediate psychosocial constructs. Addressing depression and suicidal thoughts in cancer patients would help to mitigate the risk of suicide.